Pengaruh konsentrasi larutan urin kambing sebagai media penyiraman dan pupuk organik terhadap presentase perkecambahan, persentase kecambah normal dan produksi hijauan segar pada fodder jagung (zae mays) dengan sistem hidroponik - Tri Ida Wahyu Kustyorini; Aju Tjatur Nugroho Krisnaningsih; Wempilianus Bai Ria (Jurnal Sains Peternakan, 2019)
The purpose of this study was to determine the effect of goat urine concentration. as watering media and organic fertilizer on the percentage of germination, percentage of normal germination and fresh forage production. The material used in this study was 250 corn seeds per unit. The research method used was a field experiment using a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments performed were P0 Watering 100% water, P1 watering 5% goat urine solution, P2 watering 10% goat urine solution, P3 watering 15% goat urine solution, and P4 watering 20% ​​goat urine. Based on the results of the study showed that the concentration of goat urine solution as a watering medium and organic fertilizer had a very significant effect (P<0.01) on the percentage of germination, percentage of normal germination, fresh forage production. The highest percentage of germination in P1 treatment with a value of 64.88%, the highest percentage of normal germination in P1 treatment with a value of 96.87%, and the highest fresh forage production in P1 treatment with a value of 138.8 grams. The conclution of the research were the frequency of seeding twice a day giving the highest productivity of corn (Zae mays) with hydroponic systems.